2017
DOI: 10.1002/clc.22668
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term outcome following remote ischemic postconditioning during percutaneous coronary interventions—the RIP‐PCI trial long‐term follow‐up

Abstract: The clinical value of ischemic conditioning during percutaneous coronary intervention (PCI) and mode of administration is controversial. Our aim was to assess the long-term effect of remote ischemic postconditioning among patients undergoing PCI. We randomized 360 patients undergoing PCI who presented with a negative troponin T at baseline into 3 groups: 2 groups received remote ischemic postconditioning (with ischemia applied to the arm in 1 group and to the thigh in the other group), and the third group acte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 40 publications
1
8
0
Order By: Relevance
“…It is possible that ischemic conditioning might not be effective in humans. This is supported by many recent trials (8,21,24).…”
supporting
confidence: 70%
See 1 more Smart Citation
“…It is possible that ischemic conditioning might not be effective in humans. This is supported by many recent trials (8,21,24).…”
supporting
confidence: 70%
“…The effect of ischemic conditioning as a way of myocardial protection seemed initially promising with many small studies demonstrated dramatic effect. However, as more data is gathered, the benefit of ischemic conditioning seems more controversial (7,8).…”
mentioning
confidence: 99%
“…A possible mechanism is thought to be associated with endothelial dysfunction in cerebral ischemia ( 7 ). Remote ischemic postconditioning (RIP) in the treatment of CVD relieves ischemia/reperfusion (I/R) injury ( 8 10 ). However, it is not known if RIP induces neuroprotection against cerebral ischemia and what the underlying mechanism is.…”
Section: Introductionmentioning
confidence: 99%
“…Because reperfusion injury plays a significant role in a patient's outcome, a great deal of focus has been directed toward cardioprotection by ischemic pre-, per-, and postconditioning, yielding disparate results in terms of potential therapies. Although pharmacological approaches have not translated into therapies (26) and most postconditioning trials have not produced positive outcomes (12,32), some recent trials using perconditioning strategies have shown promise (44).…”
Section: Introductionmentioning
confidence: 99%